2013
DOI: 10.1177/1062860613496135
|View full text |Cite
|
Sign up to set email alerts
|

Preventability of 30-Day Readmissions for Heart Failure Patients Before and After a Quality Improvement Initiative

Abstract: The objective of this study was to estimate the frequency of heart failure (HF) readmissions that can be prevented through a quality improvement (QI) program. All HF patients at the University of Connecticut Health Center who had a readmission within 30 days of discharge in the year before (2008) and the year after (2011) a QI program were studied. Through chart review, the percentage of patients who had preventable readmissions in each year was estimated. Prior to the QI initiative, chart reviewers identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…This allowed use of their different backgrounds in choosing which elements of the clinical record to focus on. ’ [33]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This allowed use of their different backgrounds in choosing which elements of the clinical record to focus on. ’ [33]…”
Section: Resultsmentioning
confidence: 99%
“…Several studies used an existing tool, like the STate Action on Avoidable Rehospitalizations (STAAR) initiative [14, 21, 27, 30, 34] or root cause approach [5, 18, 24, 3537] but all others adapted an existing tool or developed their own tool based on previous publications. For the purpose of this article we focused only on the distinction between studies using an a priori preventability cause classification [1316, 19, 2126, 31, 35, 3755], or not [5, 17, 18, 20, 2730, 32, 33, 36, 5659], see Table 2 . As an example of an a priori cause classification, Clarke et al reported, Unavoidable causes: chronic or relapsing disorder; unavoidable complication, readmission for social or psychological reason, reasons probably beyond control of hospital services, completely different diagnosis from previous admission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly in recently discharged patients, optimal followup decreases significantly readmission rates; the implementation of a 7 day follow-up visits programme in a tertiary US hospital as a means of quality improvement resulted in a 30% decrease of HF 30 day readmission rate. 13,14 Regular monitoring may detect disease progression and/or complications or deterioration of symptoms that may require a change in management (e.g. the onset of atrial fibrillation or development of anaemia).…”
Section: Treatment and Follow-up Protocolsmentioning
confidence: 99%
“…[26] Two studies found that a quality improvement heart failure checklist tool was effective in lowering readmission rates. [27,28] A 2014 study reviewed literature on successful readmission reduction strategies. This study found that monitoring symptoms after discharge, providing social and community support, and educating patients to promote self-management helps reduce readmissions.…”
Section: Evolution Of Readmission Reduction Strategiesmentioning
confidence: 99%